Association between night-shift work, sleep quality and health-related quality of life: a cross-sectional study among manufacturing workers in a middle-income setting. Issue 9 (6th September 2020) - Lim, Yin Cheng; Hoe, Victor C. W.; Darus, Azlan; Bhoo-Pathy, Nirmala
Abstract : Objectives: Night-shift work may adversely affect health. This study aimed to determine the impact of night-shift work on health-related quality of life (HRQoL), and to assess whether sleep quality was a mediating factor. Design: A cross-sectional study. Setting: 11 manufacturing factories in Malaysia. Participants: 177 night-shift workers aged 40–65 years old were compared with 317 non-night-shift workers. Primary and secondary outcomes: Participants completed a self-administered questionnaire on socio-demographics and lifestyle factors, 12-item Short Form Health Survey V.2 (SF-12v2) and the Pittsburgh Sleep Quality Index (PSQI). The Baron and Kenny's method, Sobel test and multiple mediation model with bootstrapping were applied to determine whether PSQI score or its components mediated the association between night-shift work and HRQoL. Results: Night-shift work was associated with sleep impairment and HRQoL. Night-shift workers had significantly lower mean scores in all the eight SF-12 domains (p<0.001). Compared with non-night-shift workers, night-shift workers were significantly more likely to report poorer sleep quality, longer sleep latency, shorter sleep duration, sleep disturbances and daytime dysfunction (p<0.001). Mediation analyses showed that PSQI global score mediated the association between night-shift work and HRQoL. 'Subjective sleep quality' (indirect effect=−0.24, SE=0.14 and bias corrected (BC) 95% CI −0.58 to −0.01) and 'sleep disturbances' (indirect effect=−0.79, SE=0.22 and BC 95% CI −1.30 to −0.42) were mediators for the association between night-shift work and physical well-being, whereas 'sleep latency' (indirect effect=−0.51, SE=0.21 and BC 95% CI −1.02 to −0.16) and 'daytime dysfunction' (indirect effect=−1.11, SE=0.32 and BC 95% CI −1.86 to −0.58) were mediators with respect to mental well-being. Conclusion: Sleep quality partially explains the association between night-shift work and poorer HRQoL. Organisations should treat the sleep quality of night-shift workers as a top priority area for action to improve their employees' overall wellbeing.